The charaktêres in Ancient and Medieval Jewish magic - Bohak, Gideon (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper examines the different magical signs found in Jewish magical texts and artifacts in Antiquity and the Middle Ages. These include especially the Graeco-Egyptian “charaktêres” (ring-letters, Brillenbuchstaben), the Arabic “string letters” (or Siegel), and the Latin sigilla or figurae, to which one may add a few other types of magical signs. This paper surveys their appearance in Jewish magical texts of different times and places, and analyzes their function within the magical texts where they are found.